Chronic green tea consumption decreases body mass, induces aromatase expression and changes proliferation and apoptosis in adult male rat adipose tissue. - Monteiro, Rosário (2008)
Green tea (GT) and its components have been shown to possess antiobesity properties and the corresponding mechanisms of action are being investigated, given the epidemic proportions of obesity incidence. In the current work, we used 12-mo-old male Wistar rats to test the effect of 6 mo of treatment with GT as the sole drinking beverage (52.8 +/- 6.4 mL/d) on adipose tissue (AT). AT aromatase expression was determined by Western blotting, plasma concentrations of 17beta-estradiol and testosterone were determined by RIA, and adipocyte size determined by measuring diameter in tissue sections. Proliferation and apoptosis were also assessed by Ki67 immunostaining and terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end-labeling, respectively. Evaluations were made in subcutaneous (sc) AT and visceral (v) AT. Body weight increased over time in both groups (P < 0.001), but the increase was more pronounced in controls (P < 0.001) and food and fluid intake did not influence that effect. At the end of the experiment, aromatase expression increased in the AT (318.5 +/- 60.6% of control in scAT, P < 0.05, and 285.5 +/- 82.9% of control in vAT, P < 0.01). AT of GT-treated rats had a higher percentage of proliferating cells (204.1 +/- 19.5% of control in scAT, P < 0.01, and 246.6 +/- 50.2% of control in vAT, P < 0.01) and smaller adipocytes (78.3 +/- 1.7% of control in scAT, P < 0.001, and 87.9 +/- 3.2% of control in vAT, P < 0.05). GT also increased the number of apoptotic cells in vAT (320.4 +/- 21.9% of control; P < 0.001). These results suggest new mechanisms for GT on body weight and highlight its potential benefit to prevent or treat obesity and the metabolic syndrome.